2006
DOI: 10.1248/yakushi.126.1139
|View full text |Cite
|
Sign up to set email alerts
|

ステロールを用いる生物活性化合物の合成と構造活性相関

Abstract: Sterols are widely and abundantly distributed in nature. It is convenient to utilize them for the preparation of useful compounds such as pharmaceuticals with steroid and secosteroid skeletons. This paper describes the synthesis and structure-activity relationships of naturally occurring active forms of vitamin D analogues, sterols having neurite outgrowth activity, and liver X receptor agonist. The active form of vitamin D 4 showed similar biological activities but had higher a‹nity to the vitamin D-binding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 71 publications
0
3
1
Order By: Relevance
“…Inspection of these two chemical structures suggests that the conjugated double bond system is essential for anti-inflammatory activity. Ergosterol, which is known as provitamin D2, is particularly abundant in fungi as well as being present in bacteria and plants [22]. However, DHE, discovered in the present study, is found only in P .…”
Section: Discussioncontrasting
confidence: 47%
“…Inspection of these two chemical structures suggests that the conjugated double bond system is essential for anti-inflammatory activity. Ergosterol, which is known as provitamin D2, is particularly abundant in fungi as well as being present in bacteria and plants [22]. However, DHE, discovered in the present study, is found only in P .…”
Section: Discussioncontrasting
confidence: 47%
“…Also, β-sitosterol (3) has no double bond between C22 and C23, and an ethyl group attaches to C24. It has been reported that some steroidal compounds express thier biological activities in vivo, caused by the reaction between their double bonds in the side chain and protein or peptide [17]. Considering its possibility, stigmasterol (1) may express its antibacterial activity by the similar way.…”
Section: Resultsmentioning
confidence: 99%
“…Dehydroergosterol was also discovered as a component of Camembert cheese that suppressed microglial inflammation. Dehydroergosterol is an analogue of ergosterol, which is a sterol found in the cell membrane of fungi [ 69 , 70 ] ( Figure 1 ). Dehydroergosterol is generated by fungi during fermentation.…”
Section: Effects Of Oleamide and Dehydroergosterol Generated Durinmentioning
confidence: 99%